THE ANALYSIS OF THEME AND RHEME IN SHORT STORY OF SLEEPING BEAUTY WITH A SYSTEMIC FUNCTIONAL APPROACH - Tarina Dashela (SALEE: Study of Applied Linguistics and English Education, 2021)
This paper is about theme and rheme in the text of short story as approach using a Functional Grammar. The aims of this study are to identify theme and rheme, to classify the types and components of theme and to describe the correlation both theme and text development. The method used in this research is qualitative method. The data is taken from a short story entitled Sleeping Beauty by Charles Perrault. The data were analysed using some theories based on a Functional English Grammar. The findings of the research are there are two types of theme (Topical and Textual Theme) that could be found while Interpersonal theme couldn’t be found in the data. Moreover, the components of theme in the category of textual theme are conjunctive adjunct, conjunctive, structural, continuative and conjunction. Meanwhile for topical theme, the components of theme are as subject and marked topical theme (adverbial as theme). To know the correlation theme and text development, the researcher has identified and classified the text of short story. Therefore, in the Theme-Rheme structure of a text clause by clause, to gain an insight into its texture and understand how the writer clarify the nature of his underlying concerns.